The Disruption of NMDAR/TRPM4 Death Signaling with TwinF Interface Inhibitors: A New Pharmacological Principle for Neuroprotection - Jing Yan; Hilmar Bading (MDPI AG, 2023)
With the discovery that the acquisition of toxic features by extrasynaptic NMDA receptors (NMDARs) involves their physical interaction with the non-selective cation channel, TRPM4, it has become possible to develop a new pharmacological principle for neuroprotection, namely the disruption of the NMDAR/TRPM4 death signaling complex. This can be accomplished through the expression of the TwinF domain, a 57-amino-acid-long stretch of TRPM4 that mediates its interaction with NMDARs, but also using small molecule TwinF interface (TI) inhibitors, also known as NMDAR/TRPM4 interaction interface inhibitors. Both TwinF and small molecule TI inhibitors detoxify extrasynaptic NMDARs without interfering with synaptic NMDARs, which serve important physiological functions in the brain. As the toxic signaling of extrasynaptic NMDARs contributes to a wide range of neurodegenerative conditions, TI inhibitors may offer therapeutic options for currently untreatable human neurodegenerative diseases including Amyotrophic Lateral Sclerosis, Alzheimer's disease, and Huntington's disease.